Towards Indonesia Halal Tourism - Atang Abd Hakim; Hasan Ridwan; M Hasanuddin; Sofian Al-Hakim (AHKAM : Jurnal Ilmu Syariah, 2017)
The background of this research is the increasingly halal phenomenon of halal tourism development. This study aims to determine and criticize the nature of halal tourism and know the indicators that can be used to measure the happiness of a kosher tourist destination. The research method used in this research is qualitative method. This study concludes that there has been a change in the nomenclature of sharia tourism into halal tourism. The concept of halal tourism has principles derived from the Qur’an and Sunnah. At the beginning of its development in 2013, the Ministry of Tourism with DSN-MUI has determined the criteria of halal tourism that includes nine principles, namely the benefit of the ummah; enlightenment, refreshment and tranquility; avoid idolatry, khurafat and immoral; maintaining the behavior, ethics and noble values of humanity; maintaining trust, safety and comfort; universal and inclusive; preserving the environment; and respect for sociocultural values and local wisdom. DOI: 10.15408/ajis.v17i2.624310.15408/ajis.v17i2.6243